Primary amenorrhoea: the ambiguous non-entity. Issue 6078 (2nd July 1977) - Ginsburg, J; Scadding, G; Havard, C W
Abstract : Hypothalamic-pituitary activity was investigated in 20 women with primary amenorrhoea, in whom gonadal dysgenesis and lower Müllerian duct anomalies had been excluded. There was no specific or uniform pattern of response to luteinising hormone-releasing hormone and no evidence of a common defect at pituitary-hypothalamic level to account for the absence of spontaneous menstruation. Six women had hyperprolactinaemia; of these five had radiological evidence of pituitary enlargement. The conventional distinction between "primary" and "secondary" amenorrhoea should be abandoned, and, in common with current practice for other endocrine glands, primary amenorrhoea should indicate an abnormality of the gonad itself and secondary amenorrhoea an abnormality that results from hypothalamic-pituitary dysfunction.